COMMUNITY PARTICIPATION AND POLICY EFFECTIVENESS IN URBAN FLOOD MITIGATION: EVIDENCE FROM PALEMBANG CITY, INDONESIA - Rahmat Rafinzar; Zailani Surya Marpaung; Tuty Khairunnisa; Maria Immaculata Yovita Adventy; Indah Permatasari (Universitas Pancasakti Tegal, 2025)
Urban flooding has emerged as a recurrent and escalating challenge in many Southeast Asian cities, including Palembang, Indonesia. Despite various mitigation efforts by local authorities, the effectiveness of such policies remains inconsistent, often due to limited community engagement. This study investigates the extent to which flood mitigation policies influence community participation and how this participation contributes to policy effectiveness. Employing a quantitative research design, data were collected from 81 residents across 27 flood-prone neighborhoods using structured questionnaires. Descriptive statistics, correlation analysis, and multiple regression models were employed to analyze the relationship between specific policy domains, particularly drainage improvement and waste management (P4), and levels of community engagement. The results reveal a strong positive correlation (r = 0.81) between P4 policy implementation and community participation, with regression analysis indicating that 67% of the variance in public engagement is explained by policy variables. These findings highlight the critical role of inclusive policy design, community-based monitoring, and education-driven interventions in flood risk reduction. However, challenges such as inconsistent enforcement and limited technological adoption remain. The study concludes by recommending the institutionalization of local task forces and curriculum-integrated environmental education to sustain community involvement. This research contributes to the literature on participatory disaster governance and provides actionable insights for urban policymakers and planners in the Global South.